External factors affecting blackboard learning management system adoption by students: Evidence from a historically disadvantaged higher education institution in South Africa - Matarirano, O.; Panicker, M.; Jere, N.R.; Maliwa, A. (South African Journal of Higher Education, 2021)
Learning Management Systems (LMS) have the ability to transform learning experiences of students in Higher Education Institutions (HEI). In addition to the developmental benefits, LMS assist teaching and learning during student unrests, a common feature in historically disadvantaged institutions in South Africa. Regardless of the benefits of LMS platforms such as Blackboard, the utilisation by university students at the institution under study has been very low. Applying cross sectional electronic survey, this study identifies the key factors influencing technology adoption, as identified in the General Extended Technology Acceptance Model for E-Learning (GETAMEL), behind perceived ease of use and perceived usefulness in the adoption of technology. A sample of 125 students at a historically disadvantaged institution in South Africa was considered for the study. Data was collected to understand their perceptions on use of Blackboard Learning Management System (BB) for learning. Data was analysed with SmartPLS statistical analysis software. Results show that perceived ease of use of BB is influenced by computer self-efficacy, computer amusement and computer anxiety whilst perceived usefulness of BB is influenced by subjective norm and computer enjoyment. The findings also show computer experience to significantly affect computer self-efficacy and computer self-efficacy to affect computer enjoyment. The article presents the external factors that affect the usage of LMS at one of the historically disadvantaged HEI in South Africa. HEI leadership has to prioritise the identified external factors to increase chances of acceptance and utilisation of Blackboard by learners.